Brønsted Acid Catalyzed α′‐Functionalization of Silylenol Ethers with Indoles1. (18th February 2015) - Ayala, Caitlan E.; Dange, Nitin S.; Fronczek, Frank R.; Kartika, Rendy
Abstract A new method which enables carbon–carbon bond formation at the α′‐position of silylenol ethers by using catalytic amounts of pyridinium triflate is reported. This chemistry successfully produces, structurally challenging, highly substituted indole‐containing silylenol ethers in excellent yields with complete regiocontrol, presumably through silyloxyallyl cation intermediates. Despite the use of Brønsted acid, the silylenol ether moiety does not undergo protodesilylation, thus underscoring the very mild reaction conditions.